Myofibroblast Deficiency of LSD1 Alleviates TAC-Induced Heart Failure - Huo, Jin-Ling; Jiao, Lemin; An, Qi; Chen, Xiuying; Qi, Yuruo; Wei, Bingfei; Zheng, Yichao; Shi, Xiaojing; Gao, Erhe; Liu, Hong-Min; Chen, Dong; Wang, Cong; et al. (Circulation research, 2021)
[Figure: see text].